Mempromosikan Desain Parametrik Untuk Pengajaran Arsitektur di Indonesia: Strategi Model Pembelajaran - Wendy Sunarya; Yusvika Ratri Harmunisa; Rizka Tiara Maharani; Heru Subiyantoro (RUAS, 2022)
Parametric design is a new architectural design approach which is developing for the last decade. This development is supported by the advance of digital architecture technology, allowing designers to engage in complex geometry modelling and design optimization efficiently using parametric design software. One of parametric design software, Rhinoceros-Grasshopper, has been interconnected to several building simulation packages, which gives new usefulness for architectural design process. Parametric design is likely to be a standard skill that should be possessed by Architect in the future. This study discusses parametric design application for architectural design process and its trend for the context of architectural education in Indonesia. It aims to give a strategy and model instruction for parametric design teaching, especially in the university level. Literature review and Youtube Channel exploration were conducted to discuss the implementation of parametric design. In order to examine the trend of parametric design in Indonesia, the data analysis was conducted based on channel analytics from one of Youtube channel promoting parametric design and survey aiming architecture lecturer.